Anti-acanthamoebic properties of natural and marketed honey in Pakistan - Farzana Abubakar, Yousuf; Malik Hassan, Mehmood; Malik, Abdul; Siddiqui, Ruqaiyyah Bano *; Khan, Naveed Ahmed * (Elsevier, 2016)
To determine anti-Acanthamoebic activity of natural and marketed honey samples. Natural honey samples were collected directly from the bee hive and marketed honey samples were purchased from the local market in Karachi, Pakistan. Both honey samples were tested for their flavonoid content (quercetin equivalent per g of the extract) and phenolic content (gallic acid equivalent per g). Furthermore, their antioxidant activity was determined by measuring 2,2-diphenyl-1-picrylhydrazyl. Using amoebistatic and amoebicidal assays, the effects of honey samples were tested against growth and viability of Acanthamoeba parasites. Natural honey exhibited potent amoebistatic and amoebicidal effects, in a concentration-dependent manner. Honey-treated A. castellanii showed loss of acanthopodia, following which amoebae detached, rounded up, reduced in size, decreased in cytoplasmic mass and they were observed floating in the culture medium. Importantly, honey-treated amoebae did not revive when inoculated in fresh growth medium, however glycerol-treated amoebae exhibited viable trophozoite and active growth. In contrast, marketed honey samples varied in their efficacy against A. castellanii. The proportion of flavonoid, as determined by quercetin measurements and the proportion of phenolic, as determined by gallic acid measurements was higher in natural honey compared with marketed honey. Similarly, the antioxidant activity, as determined by 2,2-diphenyl-1-picrylhydrazyl scavenging activity was higher in natural honey versus marketed honey. This study shows that natural honey has anti-Acanthamoebic properties and possesses higher flavonoid, phenolic and antioxidant properties compared with the marketed honey. These findings are of concern to the public, health officials, and to the manufacturers regarding production of honey for medical applications.